Ordinances of the Borough of Phoenixville, at 9-10, Ordinances 25-26 (1855) - (:unkn) unknown (My University, 1855)
§It shall not be lawful for any person or persons whatever to wantonly fire any gun, pistol or any other kind of firearms within the bounds of the Borough, and any person or persons so offending, upon conviction before the Burgess or either of the Justices of the Peace, shall pay a fine of five dollars for each offence, and in default of payment of said fines and costs shall be committed to the jail of Chester County: Provided, That this ordinance shall not apply to the High Constable or to any officer appointed by the Burgess or Town Council in the legal discharge of their office. Also prohibited the concealed carry of firearms
Keywords: CARRY - CONCEALED; DISCHARGE